OLDER ADULT'S SENSE OF PLACE IN CITIES: MAPS AND CAFES AS RESEARCH METHODS. (11th November 2018) - Fisher, J; Woolrych, R; Lawthom, R; Makita, M; Gunther, I; Gunther, H; Portella, A; Pereira, G
Abstract: Participatory mapping is an interactive, asset-based approach, recognising residents as experts and Knowledge Cafes provide a method to support conversations and dialogue in a range of settings. In this paper, we consider findings from the second Work Package of an ongoing ESRC- Newton funded project (2016–19) Place-Making with Older People: Towards Age-Friendly Communities. We undertook participatory mapping workshops and knowledge cafés with two hundred older adults and key service providers across six cities in Brazil and the UK with the aim of facilitating knowledge production with older adults and service providers about sense of place and ageing in place. Framework analysis generated a number of themes that were significant for older adults in terms of supporting ageing-in-place: the importance of facilitative spaces, barriers to social engagement in neighbourhoods and the significance of accessible buildings and open spaces. This paper will be of interest to academics, policy makers and practitioners.